Industrial Motion Control as a Context for Mechatronics Education - Gurocak, Hakan; Ashley Ater Kranov; Williams, Rochelle Letrice (Association for Engineering Education - Engineering Library Division Papers, 2012)
Industrial Motion Control as a Context for Mechatronics EducationHakan GurocakSchool of Engineering and Computer ScienceWashington State University Vancouver, USAAshley Ater-KranovManaging Director of Professional Services, ABETOver the past couple decades, mechanical engineering programs have made significantadvances in developing educational materials and laboratory exercises in controls andmechatronics. However, there is an important gap remaining between the academicprograms and the needs of the graduates and industry.The academic programs are heavily oriented towards control theory, board-levelelectronics, interfacing and microprocessors supplemented with laboratory equipment,such as the inverted pendulum, and projects, such as Lego robots. But industrialapplications require mechanical engineers to design machines with multiple axes thatexecute complex, high speed, high precision coordinated motion using sophisticatedmotion controllers. To design such systems students need to learn the industrial motioncontrol technology; be able to bring together control theory, kinematics, dynamics,electronics, simulation, programming and machine design; apply interdisciplinaryknowledge; and deal with practical application issues. Due to the currentcompartmentalized approach used in teaching these subjects and the emphasis onmathematical algorithms and board-level applications, most new mechanical engineeringgraduates are unable to meet the industry expectations.In this paper, we present an overview of a new modular curriculum we are designing bypartnering with industry to “teach the fundamentals”, but in the context of industrialmotion control technology and multi-axis machines. We also provide details of one of itsmodules along with assessment results and feedback from students. This project wasfunded by a grant in 2010 from the NSF-TUES program.